RETRACTED: Optoelectronic device for measuring the humidity of silkworth cocoons - Kuldashov Golibzhon; Daliyev Baxtiyorjon; Komilov Abdullajon; Tillaboev Mukhiddinjon; Khalilov Muhammadmusa (E3S Web of Conferences, 2024)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001